Parent-child sexual communication: a review of parental influences on adolescent sexual behaviour - Suhaimi, Nor Suhaida; Che Hassan, Norlizah; Arshad, Mohd Mursyid; Abdul Manaf, Rosliza (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
As our adolescent is at risk of HIV/AIDS, STDs and unwanted pregnancy, it is important for us to understand the process of sexual communication and its role in the sexual socialisation. It is believed that parents play a significant roles as change agent, serve to motivate and guide adolescent behaviour, provide valuable sources of information or advice and shape the sexual beliefs and behaviour of adolescent (Jaccard, Dittus, and Gordon, 2000). This constructs the possible for significant influences in adolescent sexual behaviour. Thus, this paper offers reflections on what parental influences possibly offered in determining adolescent sexual behaviour through parent-child sexual communication. Above all, it is a taboo issue to be covered in Malaysian context, but warrant for future researches on this controversial issue is necessary to ensure that adolescent able to form a healthy sexual lifestyle in future through effective and productive ways, particularly via parent-child sexual communication.